Analisis Visual pada Konten Instagram Halal Corner - Az Zahra, Shabrina Fitria; Ira Wirasari (JURNAL RUPA, 2023)
The halal lifestyle is a trend that is currently developing in Indonesia, but due to Muslims' not having enough awareness concerning the application of Islamic syariat to their daily lives, there are still Muslim communities that do not practice a halal lifestyle. As therefore, a halal lifestyle campaign is still necessary. Halal Corner is a group that promotes a halal way of life by using Instagram social media and sharing educational materials about it. This study tries to describe how Halal Corner content is evaluated from a fine arts perspective. In this study, a descriptive-qualitative methodology is used to give a visual analysis of the content of Halal Corner using an aesthetics-based perspective. Data collection is done through observation of uploaded published content by Halal Corner. The result of this study is an appreciative explanation and evaluation to the visual contents of Instagram Halal Corner trough the lens of creativity and utility.